Sporadic Stenotrophomonas maltophilia Respiratory Infections in Cancer Patients - Mahua Sinha1; Sumathi Gurusiddappa1*; Priyanka Shivashankar1; Junia Joseph1; Sahana Shetty1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Stenotrophomonas maltophilia is a bacterium that increasingly causes respiratory and bloodstream infections, particularly in individuals with compromised immune systems, such as cancer patients. This study investigates a series of S. maltophilia respiratory infections among cancer patients at a large hospital, aiming to describe the clinical and microbiological characteristics of these cases. Methods: We investigated cancer patients presenting with respiratory symptoms between February 1st and February 28th, 2023 in ten of whom S. maltophilia isolates were recovered from clinical specimens through microbiological culture. Identification was initially based on colony morphology, oxidase reaction, glucose fermentation, motility, and other biochemical tests, followed by confirmation using the Vitek® 2 system (BioMérieux). Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Results: Ten adult cancer patients (6 females, 4 males) developed S. maltophilia pneumonia between February 1st and February 28th, 2023. Eight patients had hematological malignancies, and two had solid tumors. All patients' infections were susceptible to treatment with trimethoprimsulfamethoxazole, and all patients recovered fully following treatment. Conclusion: We identified a cluster of S. maltophilia respiratory infections, but it did not meet the criteria for a true outbreak due to the lack of a common source and evidence of transmission between patients. Despite reinforced infection control measures, limitations in surveillance hindered identifying the source and implementing prevention strategies. This cluster emphasizes the need for vigilance in recognizing S. maltophilia infections in cancer patients, enabling timely, susceptibility-guided antimicrobial therapy.